Hū - Johnson-Phillipps, Keanna (Te Kaharoa, 2019)
The walls felt as if they were caving in on me, wrapping me up tighter than my mum did before she left me. Institutionalisation, colonization, since starting at Wayvalley High School in a rather wealthy area, I was a target. Skin so dark you’d think I was misplaced, like an abnormal white zebra with only one black stripe that ran right down its spine. Yes, I was the stripe. School was like my father, Jim Turia’s house. A place only known by 5 years old Kahu, but never forgotten after 10 whole years. Which was surprising seeing as my memory is quite bad, unless you want me to discuss the impact colonisation has had on my people and our country. Anyway, I’m sitting here amongst a flock of doves with uniforms that their parents probably washed every day. Well compared to mine anyway, my dress shirt has never seen an iron before and my pants look like Uncle Riki’s bum, saggy. Don’t get me started on my shoes, I walk in the house with bare feet every day, so Uncle doesn’t have to spend more money on another pair. I always laugh because Mrs Sherman is the epitome of my school shoes. Worn out, broken and ready to give in, though some how she still manages to walk her way through each day. She’s my music teacher, a 40ish year old Pākehā woman that looks at me like Uncle Riki’s boss looks at him. Oh yeah Uncle Riki, you could say he’s my father. He took me in after my mother and biological dad passed on, which I’m truly grateful for.